The future European Commission: The debate regarding leadership, collegiality and tasks - Andreas Maurer; Sarah Reichel; Alexandra Jonas (Stiftung Wissenschaft und Politik (SWP), 2004)
Following the European Parliament's approval, a new European Commission will start its work on November 1st in Brussels under the direction of Jose Manuel Durao Barroso of Portugal. Barroso announced a Commission that would be defined by leadership, vision and collegiality. These buzz words should be quickly filled out with concrete objectives for the decision-making process. Given the size and heterogeneity of the Commission, Barroso and his team have to deliver convincing proof of their determination to take responsibility for the core functions of the Commission as a team. This implies, above all, focusing on the general interest of the European Union and demon-strating a willingness to strengthen the Commission's role as the engine of integration, the initiator of legislation, and the guardian of the treaties and community law. (SWP Comments / SWP)
Keywords: 320